Information and Communication Technologies in health promotion actions carried out by medical students, in times of the Covid-19 pandemic: experience report (Research, Society and Development, 2023)
Inserted in several promising possibilities of action, the use of Information and Communication Technologies as an adjuvant device in initiatives in the health area has been gaining, continuously, space and prominence in health policies. With the aim of associating the potential role of technology in health education, as well as improving the representative indicators of coping by the Health at School Program, the present study aims to report the experience developed in an extension project through a descriptive experience report, retrospective and innovative. In a municipal school, the school's social networks were used to disseminate digital information leaflets, short-term educational videos and thematic interviews with guests from the health area on the internal radio. In the development of activities, healthy eating, actions to combat Aedes aegypti, vaccination against HPV and the promotion of a culture of peace, citizenship and human rights were addressed. The academic and professional community involved in the project was able to contribute to the implementation of alternative options for promoting health education to the population in the midst of the interruption of activities due to the new coronavirus pandemic.